Enhancing Victim Protection in Sexual Crime Cases Through a Case Analysis of Palembang District Court Decision No. 186/Pid.B/2022/PN.Plg - Awansyah, Awansyah; Romli, Romli; Yusuf, Hambali (Jurnal Ilmu Hukum Kyadiren, 2025)
This study aims to analyze Palembang District Court Decision No. 186/Pid.B/2022/PN.Plg in relation to the protection of victims’ rights in cases of sexual crimes. Victim protection within the criminal justice system is a crucial aspect that often faces various challenges in its implementation. This study employs a normative juridical research method with a case analysis approach.  The findings indicate that the court provided physical and psychological protection to the victim, as well as restitution to support recovery. However, challenges remain in ensuring the full realization of victims’ rights, particularly in terms of rehabilitation services and preventing repeat offenses. Moreover, the punishment imposed on the defendant is not always accompanied by adequate recovery measures for the victim. Therefore, the justice system must strengthen protection mechanisms by involving rehabilitation institutions and psychologists to achieve a more comprehensive and just legal framework.